Model Hubungan Kompetensi, Profesionalisme dan Kinerja Dosen - Resi Permanasari; Rina Moestika Setyaningrum; Siti Sundari (Universitas Muhammadiyah Sidoarjo, 2014)
University as an institutions of higher education has big role in national development framework. An attempt to prepare qualified human resources is improving the quality of education. Faculty performance attracted the attention that this caused was one of the essential components in the system of higher education. Roles, duties and responsibilities of teachers are very meaningful to produce quality resources. The excellent performance must be supported by the competence and professionalism. However, the professionalism of teachers is not always a line with professionalism. Professional-quality lecturers are low and not maximal even in class, lecturers as a lead actor so the student in classroom will become pasive. This research is aimed to test the influences of the competence to profesionalism, the influence of professionalism to the performance, and the influence of competence to the performance. This research used questionnaire which is distributed to all lecturer of economic faculty in UPN “Veteran” Jatim. The analysis used Partial Least Square test. The result showed that competence influencing to the lecturer’s professionalism, professionalism influencing to lecturer’s performance and competence influencing to the lecturer’s performance.